ÁREA FOLIAR OBTIDA POR MODELOS MATEMÁTICOS EM CULTIVARES DE PANICUM MAXIMUM - RODRIGUES, Wagner dos Santos; LIMA, Vitor Boschilia; OLIVEIRA, Jhenyfer Ferreira; CAPRISTO, Denise Prevedel; TORRES, Francisco Eduardo (ANAIS DO ENIC, 2018)
-